The Sun Sets on Old England: Contradictions in Conservative Educational Policy. Issue 3 (3rd July 2019) - Jones, Ken
ABSTRACT: The article describes the increasing discrepancy between the curriculum policies of the Conservative government and the policy directions argued for by business organisations and other advocates of a human capital perspective in education. It traces some of the origins of the current Conservative preference for cultural rather than economic goals in this area of policy, and suggests a new understanding of the relationship between neoconservative and neoliberal thinking on the educational right. It argues that a return to ideas and practices developed in the late twentieth century offers a basis for curriculum policy more productive than either human capital theory or Conservative traditionalism.